Studi Teknik Renang Gaya Dada pada Mahasiswa Pendidikan Olahraga FIK UNP - Delpiero, Samuel; Edwarsyah, Edwarsyah (ARZUSIN, 2023)
The research aims to analyze the study of breaststroke swimming techniques of FIK Unp sports education students. The type of research conducted is descriptive research or direct observation of breaststroke swimming techniques. Sampling is based on purposive sampling technique. The data source in this study was obtained through direct observation (observation) in the field through a direct value format in the field. Based on the overall research results from 36 samples of FIK UNP sports education students, the level of mastery of breaststroke swimming techniques was obtained (56.25%), classified in the Fair category.